André Malraux and Roman Gary’s Italian Reception - Genovese, Marilena (Literatūra, 2022)
This study focuses on André Malraux and Romain Gary’s Italian reception from their first introduction in Italy until today. One of the goals of the analysis is to synthesize all the publications devoted to them and to make the results of the identified work available to the readers. The other goal is to measure the interest shown in these two writers (whose existential choice presents many convergences) which has changed during the years because of the different historical contexts in which their writings have been read.